Предмет: Алгебра,
автор: anechkakuzia
(b^8+1)(b^4+1)(b^2+1)(b-1)/b^16-1
Ответы
Автор ответа:
0
Судя по всему должно быть так
(b^8+1)(b^4+1)(b^2+1)(b-1)/(b^16-1)=(b^8+1)(b^4+1)(b^2+1)(b-1)/((b^8-1)(b^8+1))=(b^4+1)(b^2+1)(b-1)/(b^8-1)=(b^4+1)(b^2+1)(b-1)/((b^4-1)(b^4+1))=(b^2+1)(b-1)/(b^4-1)=(b^2+1)(b-1)/((b^2+1)(b^2-1))=(b-1)/(b^2-1)=(b-1)/((b-1)(b+1))=1/(b+1)
Похожие вопросы
Предмет: Право,
автор: annapavlovska78
Предмет: Музыка,
автор: Aslanbek2009
Предмет: Қазақ тiлi,
автор: aizhankuldikova94
Предмет: Математика,
автор: Лея1978
Предмет: Геометрия,
автор: Tmila